ADVENTURE RACING SPORTS PRACTICED BY ELITE RAIDERS - Baena-Extremera, Antonio (2017)
Physical activities and adventure sports practiced outdoor are implemented in specific places and used specialized devices and particular equipment for every sport. Practicing climbing, kayak, ski, mountain bike (MTB) will be more adequate and they vary in terms of the environment´s conditions and characteristics. The aim of this study was to analyze and identify the raid sports focused on the equipment, facilities, and periods of the year when was accomplished. The sample included 272 elite competitors from Adventure Racing Spanish League (Liga Española de Raids de Aventura, LERA, for its acronym in Spanish.) The measurement method consisted in a previously validated self-test. The results revealed that 80.1% of the participants practiced raid sports through the year, and 69.8% used a particular equipment during sport practices. This study concludes that adventure raid competitors perform all kinds of adventure sports through the year and using specific equipment is the most common issue among competitors in the natural environment.English translation by Jeannette Soto Segura